2017
DOI: 10.1007/s12011-017-1153-5
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Induced Neurotoxicity and Alterations in Gene Expression in Human Neuroblastoma SH-SY5Y Cells

Abstract: Manganese (Mn) is an essential trace element required for many physiological functions including proper biochemical and cellular functioning of the central nervous system (CNS). However, exposure to excess level of Mn through occupational settings or from environmental sources has been associated with neurotoxicity. The cellular and molecular mechanism of Mn-induced neurotoxicity remains unclear. In the current study, we investigated the effects of 30-day exposure to a sub-lethal concentration of Mn (100 μM) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…Alternatively, or in addition, these lasting protein level changes may be mediated via epigenetic mechanisms, given that expression of several of them (e.g., TH, D2, DAT, and NET) are in part epigenetically regulated via DNA methylation (Archer, Berman, & Blum, ; Day et al, ; Groleau et al, ; Hillemacher et al, ) . This latter suggestion is supported by several studies in human neuroblastoma SH‐SY5Y cells showing that Mn exposure led to hypermethylated TH promoter and down‐regulated TH gene transcription (Gandhi, Sivanesan, & Kannan, ; Tarale et al, ). Recent evidence has also shown that TH expression can be mediated in part by the activity of c‐RET kinase, and that human neuroblastoma cells exposed to 30 µM Mn experienced a c‐RET mediated reduction in TH (Kumasaka et al, ).…”
Section: Discussionmentioning
confidence: 67%
“…Alternatively, or in addition, these lasting protein level changes may be mediated via epigenetic mechanisms, given that expression of several of them (e.g., TH, D2, DAT, and NET) are in part epigenetically regulated via DNA methylation (Archer, Berman, & Blum, ; Day et al, ; Groleau et al, ; Hillemacher et al, ) . This latter suggestion is supported by several studies in human neuroblastoma SH‐SY5Y cells showing that Mn exposure led to hypermethylated TH promoter and down‐regulated TH gene transcription (Gandhi, Sivanesan, & Kannan, ; Tarale et al, ). Recent evidence has also shown that TH expression can be mediated in part by the activity of c‐RET kinase, and that human neuroblastoma cells exposed to 30 µM Mn experienced a c‐RET mediated reduction in TH (Kumasaka et al, ).…”
Section: Discussionmentioning
confidence: 67%
“…Previously microarray analysis of human SH-SY5Y cells in response to 100 μM Mn for 30 days demonstrated upregulation of apoptotic pathways which was interpreted to be a causative mechanism for Mn-dependent chronic neuronal toxicity (Gandhi et al, 2018). Although information on the intracellular Mn concentration was not available (Gandhi et al, 2018), the Mn treatment probably resulted in higher accumulation than the 5-h treatment with 100 μM Mn that we used. Because we performed measurements before cell death was observed, the transcriptomic responses do not reflect immediate cell death.…”
Section: Discussionmentioning
confidence: 99%
“…1). Lower concentrations of 10 and 30 mM are within the normal range of intracellular manganese (Bowman and Aschner, 2014), whereas 100 mM falls within the pathologic range (Gandhi et al, 2018). Acute exposure to manganese increased the spontaneous firing frequency and suppressed the amplitude of APs (red arrows) in a concentration-dependent manner.…”
Section: Manganese Altered the Intrinsic Firing Behavior Of Midbrain Dopaminergic Neuronsmentioning
confidence: 95%